Harmonization of Reason and Revelation in the Islamic Scientific Tradition: A Study of the Concept of Integration of Knowledge at UIN KH. Abdurrahman Wahid, Ibn Tofail, and Ibn Rushd - Muhammad Muzaki; Hani Atus Soleha; Naelum Minatika; Mega Nur Fadilah; Arditya Prayogi (Aslama: Journal of Islamic Studies, 2026)
This study discusses the concept of harmonization of knowledge at UIN KH. Abdurrahman Wahid Pekalongan as a response to the challenges of modernization and globalization that often separate the spiritual, rational, and local cultural dimensions. Using a qualitative approach with a literature study method, this research thoroughly examines the philosophical basis of the harmonization of knowledge, particularly through Ibn Thufail's thoughts on the encounter between reason and revelation and Ibn Rusyd's ideas on the integration of aqli and naqli. The results of the study show that the harmonization of knowledge is an effort to unite Islamic values, scientific rationality, and local wisdom in a complementary epistemological framework. Ibn Thufail, through the story of Hayy ibn Yaqzhan, emphasizes that reason can guide humans to the truth, but it still requires the guidance of revelation. Meanwhile, Ibn Rushd emphasizes the importance of using demonstrative reason to understand revelation proportionally through the concepts of ittisal and takwil. UIN KH. Abdurrahman Wahid Pekalongan implements this paradigm through the strengthening of Islamic epistemology, curriculum integration, interdisciplinary research, and the internalization of local cultural values. This integration aims to produce graduates who are intellectually strong, spiritually profound, and socially and culturally competent. This study concludes that the harmonization of knowledge is not merely a combination of religion and science, but a methodological unification process that places revelation, reason, and cultural reality in a coherent and mutually reinforcing relationship.